Association between systemic lupus erythematosus and thyroid dysfunction: a meta-analysis. (November 2018) - Luo, W; Mao, P; Zhang, L; Yang, Z
Introduction: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease, the pathogenesis of which remains elusive. The deficiency or excess of thyroid hormone is defined as thyroid dysfunction, including (subclinical) hypothyroidism and (subclinical) hyperthyroidism. Autoimmune factors are likely to be relevant to the development of SLE and thyroid dysfunction. Recently, many studies have indicated that the prevalence of thyroid dysfunction is higher in SLE patients than in the general population. The objective of our study was to perform a systematic review and meta-analysis to find out the relationship between SLE and thyroid dysfunction. Methods: Literature databases were searched, including PubMed, Embase, Web of science, Cochrane, CNKI, CHINESE WANFANG, China Science and Technology Database (VIP). Studies comparing presence of thyroid dysfunction in SLE patients to healthy controls were extracted. All the statistical analyses were performed with STATA 12.0 software. Results: Ten studies with 10, 500 SLE patients and 44, 170 healthy controls were included in this study. The meta-analysis results showed that the prevalence of (subclinical) hypothyroidism in SLE patients was higher than in the healthy controls (hypothyroidism: OR = 2.93, 95% CI = 1.81–4.75; subclinical hypothyroidism: OR = 5.67, 95% CI = 3.50–9.18). No statistical difference of (subclinical) hyperthyroidism was found between SLE patients and controls. Conclusion: Our meta-analysis suggests that SLE is significantly associated with increased risk of (subclinical) hypothyroidism, but it has little influence on (subclinical) hyperthyroidism.